Girls think of everything : stories of ingenious inventions by women - Thimmesh, Catherine; Sweet, Melissa (Boston : Houghton Mifflin, 2000)
Tells the story of how women throughout the ages have responded to situations confronting them in daily life by inventing such items as correction fluid, space helmets, and disposable diapers.
Keywords: Women inventors -- United States -- Biography -- Juvenile literature; Inventions -- United States -- History -- Juvenile literature; Inventors; Inventions; Women -- Biography